Assessing Knowledge of Acute Respiratory Infections among Mothers of Under-Five Children in Kageshwori Manahara, Nepal - Shrestha, Rashmi (Journal of Multidisciplinary Research Advancements, 2023)
This study aimed to assess the knowledge of mothers with under-five children regarding acute respiratory infection (ARI) in Kageshwori Manahara 13. The study was conducted on 50 respondents, and a semi-structured interview was used to collect data. Results showed that 82% of respondents had heard about ARI, with most of them learning about it from themselves. However, only half of the respondents knew that ARI affects both the nose and lungs and is a communicable disease that mostly occurs in children under five years of age. More than half of the respondents believed that ARI occurs in the winter season but mainly due to dust and smoke. Interestingly, 90% of the respondents thought that antibiotics could treat ARI, and 38% believed that gargling with water was a home remedy. Despite the majority having knowledge of ARI, the study highlights the need for increased awareness campaigns and TV programs to educate people, particularly those in rural areas where basic health services are lacking. Ultimately, improving knowledge of ARI could contribute to reducing mortality rates in under-five children due to this common illness.